HERMENEUTICS IN UNDERSTANDING PHOTOS “REJANG FOR SALE” BY PUTU DUDYK - Wijaya, I Putu Sinar; Budayana, I Wayan Gede (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Photography has the term photographer, namely the person who carries out the recording. For a professional photographer, the photo object is not just a mere recording, but must provide an aesthetic touch to various compositions. Photographers are now so creative, they are not only experts in using a camera but also have to be experts in preparing photo themes and final processing to give an aesthetic impression in the feel of the photo. Photographer Putu Dudyk, as he is usually called, is a photography practitioner and lecturer. He has been involved in the world of photography for a long time, he has produced many works, including documentation and art photographs. The method used in this research is a descriptive qualitative method. dialogical hermeneutics, for him correct understanding is understanding that leads to the ontological, not methodological, level. This means that truth can be achieved not through methods, the photographic work entitled Rejang For Sale by Dudyk visualizes three rejang dancers, each of whom has their own expression according to the desired concept and theme, the addition of plastic as a symbol of packaging for a product that can be sold. bought, with a black background as an impression of sadness, as well as the dancers' sad expressions and blank stares depicting the lack of sincerity in something that is sacred being commercialized.